PENINJAUAN RISIKO BENCANA DI DESA DADAP KECAMATAN SAMBALIA KABUPATEN LOMBOK TIMUR - Pradjoko, Eko; Oktorani, Karolina Dori; Istiani, Ratna Ayu; Mar’i, Ari Kusuma; Hidayat, Boyke Feril; Aprillyana, Adhe Putri; Ashari, Rowi; Magani, Ismul Azam; Muslimin, Jihadul; Haerani, Nur (Universitas Mataram, 2024)
ABSTRACT Something that threatens and disrupts the lives of many people based on natural or non-natural factors is called a disaster. Disasters are very risky because they not only harm material things but also lives. To anticipate disasters, it is necessary to conduct a disaster risk review. Disaster risk is identified through hazard studies, namely any disaster that can cause danger. Regional vulnerability, namely regional conditions that determine the danger of disaster. Then capacity, namely the ability of available resources to face danger. Dadap village is one of the villages where disaster risk can be studied in order to become a disaster resilient village. To study all of this, methods are needed so that the risk of danger is handled appropriately. Efforts to form a task force are also a step in reducing disaster risk and preparing for disaster-resilient villages.